A retrospective study on titanium sensitivity: Patch test materials and manifestations. (24th May 2018) - de Graaf, Niels P. J.; Feilzer, Albert J.; Kleverlaan, Cees J.; Bontkes, Hetty; Gibbs, Sue; Rustemeyer, Thomas
Abstract : Background: Titanium is being increasingly used. Although it is considered to be a non‐allergenic material, allergic reactions to it have been reported. Titanium dioxide has been found to be an unreliable patch test material. Few studies to date have profiled titanium allergy, and it therefore remains difficult to distinguish its manifestations. Objectives: To evaluate alternatives for titanium dioxide as a patch test preparation, and to profile titanium reactions and manifestations. Methods: A retrospective chart review was conducted with 458 patients who underwent patch testing with at least 1 of 5 different titanium salts. Results: At least 1 positive result was noted in 5.7% of the patients. The frequency of positive results for the tested salts ranged from 0.9% to 7.9%. Titanium(IV) oxalate hydrate had the highest yield and titanium dioxide the lowest. Erythema, dermatitis and local swelling were the most common objective complaints. In 16 (61.5%) patients, the test result had partial or full clinical relevance. Conclusions: No titanium‐specific risk factors and clinical picture could be identified. Titanium dioxide is not adequately sensitive for identifying titanium allergy. The titanium salts seem to be possible superior patch test preparations, but appear to be unsuitable if used singly. The patient's medical history and clinical picture remain crucial in the diagnostic work‐up.